HIV/AIDS-Related risk behaviors, HIV prevalence, and determinants for HIV prevalence among hijra/transgender people in India: Findings from the 2014-2015 integrated biological and behavioural surveillance - Shobini Rajan; Pradeep Kumar; Bhavna Sangal; Arvind Kumar; Shreena Ramanathan; Savina Ammassari (Wolters Kluwer Medknow Publications, 2020)
Background: Hijra or transgender (H/TG) people are significantly affected by HIV in India. HIV prevalence among H/TG is the second highest after people who inject drugs. Effective interventions require understanding about various risk behaviors and associated factors for high prevalence. Objectives: This study analyzes the known risk behaviors and vulnerabilities of HIV-positive and HIV-negative H/TG people to identify the determinants of HIV seropositivity in this high-risk group. Methods: Using secondary data from India's 2014 to 2015 Integrated Biological and Behavioural Surveillance survey, this analysis was conducted among 3325 H/TG people across seven states. Probability-based sampling methods were used to recruit H/TG people. Informed consent was obtained for the collection of behavioral information and blood samples for HIV testing. Multivariable binary logistic regression analysis was undertaken to identify the determinants of HIV seropositivity. Results: HIV prevalence for this group of respondents was 9.5%. Multivariable analysis of survey data revealed higher odds of HIV infection if H/TG had regular male partners (adjusted odds ratio [AOR]: 1.81, confidence interval [CI]: 1.07-3.06), were living in the states of Maharashtra (AOR: 6.08, CI: 3.02-12.22) and Odisha (AOR: 2.91, CI: 1.05-8.06), and were members of self-help groups (AOR: 2.08, CI: 1.04-4.14). None of the demographic or behavioral correlates of risk were found to be associated with HIV infection. Conclusion: The findings suggest that community and structural factors, which are inadequately covered in surveys such as IBBS, play a more important role than individual behavioral factors.